PRODUCTION AND OPTIMIZATION OF Α-AMYLASE FROM ASPERGILLUS FLAVUS UNDER SOLID STATE FERMENTATION (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Alpha amylase is one of the important and well known industrial enzymes that cause the breakdown of starch or glycogen. Use of microorganism for the production of amylase is economical as microbes are easy to manipulate to obtain enzymes of desired characteristics. However fungus is preferred over bacteria for enzymes production because of its filamentous nature. Agricultural wastes byproducts have great potential for the production of enzymes. Two indigenous carbon sources namely wheat bran and rice bran were used as substrate for amylase synthesis by Aspergillus flavus through solid state fermentation. Wheat bran gave the highest (670 ± 36μmol./min/mL) and Rice bran (428 ± 24μmol./min/mL) gave the lowest enzyme activity was obtained. Optimum inoculum size of 10% (660 ± 36μmol./min/mL), incubation period 120 hours (670 ± 28 μmol./min/mL), pH 6 (680 ± 42μmol./min/mL), temperature at 30°C (660 ± 46μmol./min/mL) gave highest yield of enzyme production. The highest yield of amylase production was obtained by the addition of MgSO4 0.2% and CaCl2 0.02% respectively. The results obtained in the present study suggest that the Aspergillus flavus may act as a potent strain for industrial production of α-amylase.